PERAN GEREJA DALAM MENYIKAPI PERSOALAN EKOLOGI DI TAPANULI RAYA - Sinambela, Pison (Penerbit Widina, Widina Media Utama, 2025)
This research aims to analyze the ecological crisis in Tapanuli Raya and to examine the role of the church as a moral and spiritual agent in responding to environmental damage. The method used is a qualitative approach through a literature study by examining various theological, scientific, and socially relevant. The results of this research showed that the ecological crisis was caused by the excessive exploitation of natural resources, the anthropocentric paradigm, and the weakness of integrating moral and spiritual values in environmental management. The impact includes ecosystem damage, pollution, biodiversity loss, and social conflicts that are detrimental to indigenous peoples. This crisis also reflects the moral failure of man in maintaining the balance of creation and responsibility to the next generations. This research also found that the church has a strategic role in building ecological moral awareness through the teaching of creation theology and the principle of stewardship. The church functions not only as a spiritual institution but also as a prophetic power that drives mindset changes, life ethics, and concrete actions. The active involvement of the church is very important in realizing ecological justice and the sustainability of life together. ABSTRAKPenelitian ini bertujuan untuk menganalisis krisis ekologis di Tapanuli Raya serta mengkaji peran gereja sebagai agen moral dan spiritual dalam merespons kerusakan lingkungan. Metode yang digunakan adalah pendekatan kualitatif melalui studi literatur dengan mengkaji berbagai sumber teologis, ilmiah, dan sosial yang relevan. Hasil penelitian menunjukkan bahwa krisis ekologis disebabkan oleh eksploitasi sumber daya alam yang berlebihan, paradigma antroposentris, serta lemahnya integrasi nilai moral dan spiritual dalam pengelolaan lingkungan. Dampaknya meliputi kerusakan ekosistem, pencemaran, hilangnya keanekaragaman hayati, serta konflik sosial yang merugikan masyarakat adat. Krisis ini juga mencerminkan kegagalan moral manusia dalam menjaga keseimbangan ciptaan dan tanggung jawab terhadap generasi mendatang. Penelitian ini menemukan bahwa gereja memiliki peran strategis dalam membangun kesadaran moral ekologis melalui ajaran teologi penciptaan dan prinsip stewardship. Gereja tidak hanya berfungsi sebagai lembaga spiritual, tetapi juga sebagai kekuatan profetis yang mendorong perubahan pola pikir, etika hidup, dan tindakan nyata. Keterlibatan aktif gereja menjadi penting dalam mewujudkan keadilan ekologis dan keberlanjutan kehidupan bersama.